Comparison of soil index properties value for different pre-drying conditions on clayey soil - Teing, Chai Yoon (2015)
Pre-drying of soil samples prior to index properties testing plays an important role in order to obtain accurate and reliable results. Most of the soil engineering properties are correlated with index properties values for investigation of soils behavior and characteristics. According to British Standard, BS1377:1990-Part 1, soil shall be dried by either air drying or oven drying before testing. However, for some soils, their physical properties may change permanently under high temperature especially plasticity index and shrinkage limit. Permanent alteration of soil physical properties will eventually influence the characteristic and behavior of the soil. Many definitive procedures require that soil should be used at its natural state, not be allowed to become dry before testing. Hence, effect of pre-drying conditions on the soil index properties is studied on three number of disturbed clayey soil samples pre-treated in five (5) different pre-drying conditions at different temperatures and drying duration. Soil specimens were tested based on index properties including moisture content, Atterberg limit, linear shrinkage, particle size distribution and specific gravity accordance to BS1377:1990-Part 2. The results obtained revealed that increase of pre-drying temperature and duration has significant effect on the plasticity index of about 13% and shrinkage limit of about 4% on the clayey soil consisted higher percentage of fine particles which also influence the classification of the clayey soils. Conclusively, oven drying method should not be used in soil preparation for plasticity and shrinkage testing.